2023
DOI: 10.1186/s12961-023-01010-9
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative analysis of factors influencing the implementation of antiretroviral treatment adherence policy in Ghana: stakeholders perspective

Martha Ali Abdulai,
Fraukje E. F. Mevissen,
Veerle Marien
et al.

Abstract: Background The Joint United Nations Programme on HIV/AIDS launched the 90-90-90 initiative. Failure to meet the target reflects the difficulties in successfully implementing HIV treatment policy. There are research gaps in exploring personal and external factors influencing HIV treatment in Ghana. To fill this gap, we explored individual and environmental (interpersonal, community and structural) factors influencing stakeholders' HIV treatment policy implementation in Ghana. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In a study conducted in India in 2011, it was elucidated that treatment adherence in PLHIV might be considerably influenced by many social, individual, and family environmental factors [22]. Studies conducted in Ghana have also indicated that treatment adherence is influenced by both individual and environmental factors [23]. The findings of previous studies have identified several clinical variables that have an impact on ART adherence [24].…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted in India in 2011, it was elucidated that treatment adherence in PLHIV might be considerably influenced by many social, individual, and family environmental factors [22]. Studies conducted in Ghana have also indicated that treatment adherence is influenced by both individual and environmental factors [23]. The findings of previous studies have identified several clinical variables that have an impact on ART adherence [24].…”
Section: Introductionmentioning
confidence: 99%